2006
DOI: 10.1038/sj.bjc.6603458
|View full text |Cite
|
Sign up to set email alerts
|

Animal food intake and cooking methods in relation to endometrial cancer risk in Shanghai

Abstract: We evaluated animal food intake and cooking methods in relation to endometrial cancer risk in a population-based case -control study in Shanghai, China. A validated food frequency questionnaire was used to collect the usual dietary habits of 1204 cases and 1212 controls aged 30 -69 years between 1997 and 2003. Statistical analyses were based on an unconditional logistic regression model adjusting for potential confounders. High intake of meat and fish was associated with an increased risk of endometrial cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 41 publications
3
61
0
Order By: Relevance
“…As will be discussed below, the generation of Maillard reaction products contributes to reducing protein digestibility. Moreover, as precursors to mutagenic heterocyclic amines, Maillard reaction products have been associated with numerous physiological problems, including pancreatic (Anderson et al, 2002), colorectal (Murtaugh et al, 2004;Sinha et al, 2005) and endometrial (Xu et al, 2006) cancers. Why we should be attracted to specific flavors at all remains unknown, but it is particularly surprising that we should demonstrate a distinct preference for flavors associated with apparently detrimental compounds.…”
Section: Increased Food Intakementioning
confidence: 99%
“…As will be discussed below, the generation of Maillard reaction products contributes to reducing protein digestibility. Moreover, as precursors to mutagenic heterocyclic amines, Maillard reaction products have been associated with numerous physiological problems, including pancreatic (Anderson et al, 2002), colorectal (Murtaugh et al, 2004;Sinha et al, 2005) and endometrial (Xu et al, 2006) cancers. Why we should be attracted to specific flavors at all remains unknown, but it is particularly surprising that we should demonstrate a distinct preference for flavors associated with apparently detrimental compounds.…”
Section: Increased Food Intakementioning
confidence: 99%
“…In addition, we found nine case-control studies evaluating this association [9,20,22,[33][34][35][36][37][38]. Of these, six suggested elevated risk [9,20,22,34,37,38], whereas in the other three studies, odds ratios for meat intake were one [33,36] or below one [35]. It should be noted that the definition of meat varied substantially by study, as shown in the Appendix Table. Furthermore, three of the studies [20,22,35] did not adjust for total energy intake.…”
Section: Meat (Type Unspecified)mentioning
confidence: 99%
“…The Iowa Women's Health Study found no association [29], whereas the other cohort study conducted in Finland [32] suggested increased risk associated with fried meat intake, but the confidence interval included the null value. In addition, we found nine case-control studies evaluating this association [9,20,22,[33][34][35][36][37][38]. Of these, six suggested elevated risk [9,20,22,34,37,38], whereas in the other three studies, odds ratios for meat intake were one [33,36] or below one [35].…”
Section: Meat (Type Unspecified)mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, when the role of nutrients is considered, the evidence is far from consistent. 5,7,[17][18][19] This may be due to the high correlations that exist between dietary nutrients, which have made it difficult to distinguish the effect of individual nutrients.…”
mentioning
confidence: 99%